STUDENTS’ PERCEPTION OF LECTURERS’ ROLE IN ENHANCING EFL LEARNERS’ COMMUNICATION ABILITY: A STUDY AT EIGHT SEMESTER ON ACADEMIC YEAR 2018 IN IAIN CURUP - Budiman, Wisnu; Apriani, Eka (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
The main goal of this study was to investigate about lecturer’s role in teaching speaking for enhancing students’ communication ability. The researcher employed descriptive quantitative method which was to know the students’ perception on lecturers’ roles to achieve students’ communication ability. Then, the researcher chose three lecturers of speaking subject to know about students’ perception on lecturers’ roles in enhancing EFL learners’ communication ability as the purpose of teaching speaking skill. The result shows that the majority of students’ perception was in positive category when the lecturers play the various roles in assisting students to improve their communication ability. However, Lecturer “A” still need to be more maximize his role as need analyst and Lecturer “B” also need to consider his role as manager in teaching speaking, because both of lecturers got neutral perception. Thus, the lecturers’ role is crucial for improving students’ communication ability.